Biased antagonism of a series of bicyclic CXCR2 intracellular allosteric modulators - Van Bosstraeten, Brent; Boon, Katrijn; Van Hoof, Max; Dehaen, Wim; Szpakowska, Martyna; Chevigné, Andy; Schols, Dominique; De Jonghe, Steven; Van Loy, Tom (Frontiers in Pharmacology, 2025)
Targeting the human chemokine receptor (CXCR2) holds significant potential in treating inflammatory diseases and cancer. In this study, we investigate the biased properties of previously reported CXCR2 antagonists (i.e., the MVH compounds). These antagonists likely bind to a conserved intracellular pocket that is also targeted by the well-known CXCR2 antagonist, navarixin. However, unlike navarixin, the MVH compounds are derived from a completely distinct chemotype, raising the possibility that they may engage the receptor differently and produce biased inhibition of downstream signaling pathways. To deduce these potential biased properties, the compounds were investigated using two NanoBRET-based assays, showing a preferential inhibition of CXCR2-mediated β-arrestin recruitment over G protein activation. Furthermore, a detailed statistical analysis revealed an additional bias in the inhibition profiles dependent on the specific ELR+ chemokine used to stimulate the receptor. Altogether, these results describe the MVH compounds as the first set of biased CXCR2 intracellular antagonists.